1228 Executive Functions at 10–15 Years in Children Born at < 26 Weeks' Gestation After Active Perinatal Care: Uppsala-UmeÅ Study. (October 2012) - Karlsson, J; Hagglof, B; Farooqi, A
Abstract : Aim: To determine the nature, frequency and severity of executive dysfunction (EDF) in 10 to 15-year-old extremely preterm (EPT) children born at 2 tertiary care centers in Sweden adhering to a policy of universal resuscitation of all infants born alive. Design/methods: The outcomes of 121 surviving EPT (86% of all EPT survivors) children born 1992 through 1998 were compared to a matched control of children born at term. Cognitive function was assessed by WISC-III. Executive functions were assessed by D- KEFS Tower of London and ADHD-symptoms by Conners 10-item rating scale. Relationship of perinatal risk factors (PNRF) with the outcomes was examined with appropriate statistical analyses. Results: The EPT children exhibited significant EDF compared with their controls in many EFs such as impulsivity, inattention and planning ability even after controlling for intelligence (IQ). Mean scores in EPT and controls were, respectively, 79 vs 101 in full scale IQ, P<0.001; 2.5 vs 0.5, P<0.001 in Impulsivity; 9.1 vs 11.8, P<0.001 in planning ability; and 4.4 vs 1.62 in ADHD symptoms. Severe impairments were exhibited in only a small minority of EPT children. No statistical conclusions were altered when children with substantial neurosensory impairment were excluded. Relation of PNRF will also be discussed. Conclusions: School-aged children who were born EPT in the 1990s are at greater risk for developing EDF and these contribute excess morbidity over cognitive impairment in EPT children. Thus these children require ongoing neuropsychological review throughout their childhood and adolescence.